TRAINING MODULE EFFECTS ON ENHANCING TEACHERS' UNDERSTANDING IN IMPLEMENTING MERDEKA CURRICULUM FOR EARLY CHILDHOOD EDUCATION - Alfian Rahmatullah; Sukiman; Nur Aizah; Ida Maulida; Anggraini; Muthi'ah Jihadillah Saepurohman (Universitas Panca Sakti Bekasi, 2024)
This study aimed to evaluate the impact of Community Service (PKM) in the form of training for Early Childhood Education (ECE) teachers regarding the implementation of the Merdeka Curriculum. This PKM training was consistently conducted by Master's students in ECE from Pancasakti University Bekasi for ECE teachers affiliated with HIMPAUDI in the Tebet District. Two instructional modules were utilized in this training: Introduction to Intracurricular Teaching Modules and the execution of the Pancasila Student Profile Strengthening Project (P5). The research method employed was quantitative, involving the collection of pre-test and post-test data distributed among the training participants. The research findings indicate that the PKM training significantly contributed to improving teachers' understanding of the implementation of the Merdeka Curriculum in the ECE environment. With an N-Gain Score of 69.61%, it highlights the substantial positive impact of the PKM training intervention on enhancing teachers' comprehension of the Merdeka Curriculum.